2016
DOI: 10.1016/j.ijid.2016.02.839
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR of whole blood specimens transported in PrimeStore MTM® to detect and monitor MTB bacteremia

Abstract: studied. Aerosol therapy in mice is problematic due to the high cost of the required apparatus. The purpose of this study was to explore the efficacy of intranasal (IN) administration (as a surrogate for aerosol delivery) of isoniazid (INH) and rifalazil (RZL) in a murine tuberculosis model compared to oral delivery.Methods & Materials: Six week old female Balb/c mice (purchased from Charles River Laboratories, Wilmington, MA) were infected intranasally with about 10 3 CFU of Mycobacterium tuberculosis (MTB) A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Several commercially available Viral Transport Mediums (VTMs) contain a chemical inactivation ingredient. These include the Primestore ® Molecular Transport Medium (MTM) [ 6 ], which is a United States Food and Drug Administration (FDA)-registered VTM (USA) that has been demonstrated to effectively inactivate and preserve multiple pathogens, including mycobacterium tuberculosis (MTB) [ 7 ] and influenza virus [ 8 ], and does not compromise the sensitivity of the GeneXpert platform in the detection of MTB or first-line MTB rifampicin (RIF) resistance (MTB/RIF assay) [ 9 , 10 ]. COPAN™, another VTM, is registered as a non-propagating transport and culture medium with the FDA but does not contain any inactivating agents [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several commercially available Viral Transport Mediums (VTMs) contain a chemical inactivation ingredient. These include the Primestore ® Molecular Transport Medium (MTM) [ 6 ], which is a United States Food and Drug Administration (FDA)-registered VTM (USA) that has been demonstrated to effectively inactivate and preserve multiple pathogens, including mycobacterium tuberculosis (MTB) [ 7 ] and influenza virus [ 8 ], and does not compromise the sensitivity of the GeneXpert platform in the detection of MTB or first-line MTB rifampicin (RIF) resistance (MTB/RIF assay) [ 9 , 10 ]. COPAN™, another VTM, is registered as a non-propagating transport and culture medium with the FDA but does not contain any inactivating agents [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The secondary objective of this study was to evaluate the ability of MTM to inactivate BCG in spiked milk samples as well as its ability to preserve BCG DNA for PCR-based diagnostics. According to previous reports, PrimeStore ® MTM was an efficient storage and transport medium for the inactivation of bacteria, fungi, and viruses as well as stabilizing and preserving the nucleic acids for molecular testing [ 26 , 27 , 28 ]. In line with other studies, samples preserved in MTM showed no mycobacterial growth after 8-week incubation on solid media compared to the positive control where mycobacterial colonies were observed after 2–3 weeks incubation [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prime Store MTM is composed of an optimized blend of chelating, chaotrophic detergents, and electrolyte reagents specifically formulated for sample inactivation, lysis of biological pathogens, and stabilizing and preserving released nucleic acids for a prolonged time. Previous studies have shown that MTM effectively inactivated several viruses, fungi, and bacteria, including M. tuberculosis , and preserved nucleic acids at ambient temperature for downstream molecular testing [ 26 , 27 , 28 ]. Based on the potential utility of MTM for collection, transportation, and inactivation of potentially infectious pathogens, the secondary objective of this study was to evaluate the ability of MTM to inactivate M. bovis BCG, as well as to preserve BCG DNA for PCR-based diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…We propose the use of IMTM for other gastrointestinal pathogen detection like norovirus, astrovirus, sapovirus, adenovirus and other enteroviruses. A similar product Longhorn PrimeStore® has been used for Mycobacterium tuberculosis, vibrio, rotavirus and influenza virus detection through Genexpert and next generation sequencing 4,5,6,7,8,9 (NGS).…”
Section: Methodsmentioning
confidence: 99%
“…Longhorn PrimeStore® is an approved molecular transport medium from Center for Disease Control CDC, USA having guanidine thiocyanide as basic ingredient which is utilized to collect and transport good quality nucleic acid for PCR based molecular diagnostics. It is also proven to be used for genomic applications other 4,5,6,7,8,9 than PCRs.…”
Section: Introductionmentioning
confidence: 99%